2018
DOI: 10.4253/wjge.v10.i10.294
|View full text |Cite
|
Sign up to set email alerts
|

Economical effect of lumen apposing metal stents for treating benign foregut strictures

Abstract: AIMTo evaluate the clinical and economical efficacy of lumen apposing metal stent (LAMS) in the treatment of benign foregut strictures.METHODSA single center retrospective database of patients who underwent endoscopic treatment of benign foregut strictures between January 2014 and May 2017 was analyzed. A control group of non-stented patients who underwent three endoscopic dilations was compared to patients who underwent LAMS placement. Statistical tests performed included independent t-tests and five-paramete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…A 15×10-mm LAMS was the most commonly used stent, with median stent dwell time varying from 60-119 days. Our study quality assessment found that 11 were of medium quality [ 14 - 18 , 21 , 22 , 24 , 26 - 28 ] and 7 were of low quality [ 11 - 13 , 19 , 20 , 23 , 25 ] ( ).…”
Section: Resultsmentioning
confidence: 98%
“…A 15×10-mm LAMS was the most commonly used stent, with median stent dwell time varying from 60-119 days. Our study quality assessment found that 11 were of medium quality [ 14 - 18 , 21 , 22 , 24 , 26 - 28 ] and 7 were of low quality [ 11 - 13 , 19 , 20 , 23 , 25 ] ( ).…”
Section: Resultsmentioning
confidence: 98%
“…The high reintervention rate raises concern about the cost-effectiveness of LAMS in the management of benign GI strictures, given the fact that LAMS placement is an expensive procedure. In a study evaluating the economical efficacy of LAMS in the management of benign GI strictures, Hallac et al found that LAMS placement may have an economic advantage over recurrent dilation after the third dilation [ 17 ]. In the present study, most of the strictures had already failed previous treatments.…”
Section: Discussionmentioning
confidence: 99%
“…Lumen-apposing metal stents (LAMS) are short, fully covered metal stents with large flanges at each end to anchor the stent and minimize migration risk [53,54]. Initially designed for draining pancreatic fluid collections, LAMS has been used off-label to manage short-segment luminal strictures [55,56], with several studies showing promising outcomes.…”
Section: Lumen-apposing Metal Stentsmentioning
confidence: 99%